TRANSFORMASI EDUKASI KESEHATAN MELALUI IMPLEMENTASI POJOK LITERASI INFORMATION TECHNOLOGY DI SMP TRI BHAKTI TEGALDLIMO - Levy Andika; Dewi Wulan; Diansanto Prayoga (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Technological transformation has become a national priority, yet adolescent health literacy in Indonesia remains low due to the dominance of conventional educational methods. Digital media such as Canva offers effective solutions for health information visualization. This community service program aimed to evaluate the effectiveness of the Information Technology Literacy Corner using a one-group pretest-posttest design to enhance students' health knowledge. The Project-Based Learning approach was implemented across two sessions targeting 21 PMR and OSIS members at SMP Tri Bhakti Tegaldlimo. Data were collected via Kahoot!-based pre-tests and post-tests. Results showed substantial score improvements: first session averages rose from 72.86 to 98.57; second session from 73.33 to 100.00. The Information Technology Literacy Corner successfully transformed conventional education into interactive learning through Canva infographics and PowerPoint slides. OSIS and PMR leaders are expected to independently apply these skills for sustainable peer education.